New beach geomorphic features associated with a temporal climate storm event, coinciding with the February 6, 2023, little tsunami, Ras El-Bar, Nile Delta coast, Egypt - Hesham M. El-Asmar; Mahmoud Sh. Felfla; Mariam T. Ragab; Doaa M. Naguib; Sameh B. El-Kafrawy (Geoscience Letters)
Abstract Typically, a temporal storm event, coupled with the earthquakes on February 6, 2023, in Kahramanmaraş, Turkey, and described as the little tsunami, resulted in new beach geomorphic features. The current study addresses these features, recorded at Ras El-Bar coast, using a remote sensing, field observation, beach profile surveys, and a grain size analysis. The results indicate that the beach is no longer dissipative, with slopes shifting from gentle (1.15°–1.3°) to steeper (2.10°–2.17°) and grain size coarsening from fine sand (0.18 mm–0.22 mm) to medium sand (0.28 mm–0.32 mm). Surf scaling reflects a transition from spilling breakers (ε = 24–72 between 1998 and 2022) to plunging breakers (ε = 8–14 between 2023 and 2024). This shift is accompanied by the formation of intermediate reflective beaches, including transverse bar-rip (TBR) (Ω = 3) and rhythmic bar and beach (RBB) (Ω = 4) morphologies. The Digital Shoreline Analysis System reveals shoreline changes, with an average erosion of − 6.1 m and accretion of 8.4 m, influenced by the shoreline’s response to protection measures. Bathymetry and shoreface profiles highlight changes in sea bottom topography with pronounced scouring. The beach exhibits rhythmic cusps spaced 3–5 m apart, rip channel transects, concave tidal flat, and a slip-faced transverse bar of mixed shells and sand. Ripple scouring linguoidal and linear shapes, with combined increased wave height and turbidity driven by a faster-falling tide, confirming the occurrence of an unusual storm event, described as a little tsunami.